Comparative study of bioethanol production from rotten grape and apple fruits as renewable energy and waste management / Norah Hammad Alhawiti - Alhawiti, Norah Hammad (2012)
Biomass of various sources such as those of cellulosic and hemicellulosic contents were proven to produced bioethanol. This study focused on the production of bioethanol from waste fruits of grapes and apples using yeast Saccharomyces cerevisiae, which is viewed as a mean of reducing environmental pollution. High bioethanol production was obtained using yeast loading of 4 g/L at 32°C after 3 days of fermentation time producing bio-ethanol 13.1% (v/v) and 9.2% (v/v) in rotten grapesand apples respectively. Bioethanol yeild was observed to decreased with increasing fertmentation time beyond 3 days, probably due to microbial wastes such as CO2 that accumulates in the fermentation media, that tends to reduced the media pH thereby inhibiting microbial growth by cyto-toxicity effect. Among the parts of friuts used as substrates, pulp was observed to produced more ethanol (13% ±0.2) as compared to the skin, probably due to low lignin content of the pulp. Comparing enzymatic hyrolysis of the fruits cellulosic content to simple sugars, amylase was observed to produced high glucose yeild (8.5 ± 0.2 mg/mL) as compared to cellulase (7.5 ± 0.2 mg/mL). The obtained bioethanol was subjected to engine test and revealed a remarkable reduction of hazardous gases (NOx, CO2, CO, SOx and HC) in the blends of bioethanol (E10, 90% pure fuel + 10% bio-ethanol). The emission tests were performed on Proton Gen 2 Multicylinder engine, with less greenhouse gasses emission in grape waste than in apple waste.